GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 07 Dec 2019, 16:42 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  # In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X

Author Message
TAGS:

### Hide Tags

Intern  Joined: 27 Aug 2014
Posts: 1
Schools: Haas '17
Re: In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X  [#permalink]

### Show Tags

FYI guys, this is a Manhattan Review Turbocharge question.
Manager  Joined: 14 Sep 2014
Posts: 86
WE: Engineering (Consulting)
Re: In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X  [#permalink]

### Show Tags

It is actually very easy
Expand Brackets
we need An/(x+...+x^5) = x^5
An = x^5 (x+...+x^5)
An = x^6+....+x^10
only n = 7 satisfies..
Intern  Joined: 27 Apr 2014
Posts: 2
Re: In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X  [#permalink]

### Show Tags

I have solved it in this way:

The question asks to find n where
An/x(1+x(1+x(1+x(1+x)))) = x^5 (1)

Factorizing An= x^(n-2)(x(1+x(1+x(1+x(1+x)))) (2)

Replacing (2) in (1) we get: X^(n-2)=x^5-->X^n=x^7-->n=7

regards
Intern  Joined: 01 Jun 2016
Posts: 1
Re: In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X  [#permalink]

### Show Tags

A different approach...

The maximum power of "x" in the denominator is 5 because "x" appears 5 times. For the ratio to be x^5, the numerator should have x^10. The highest power of "x" in the numerator is 10; so by comparison, n+3=10 => n = 7.
Manager  B
Joined: 31 Dec 2016
Posts: 65
Re: In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X  [#permalink]

### Show Tags

I think the question was harder because the original person didn't write it in clear notation. Using Bunnel's look makes it solvable.

I didn't solve here but I am explaining the math for those that don't get why when you remove an X^n-1 that it looks the way it does.
Attachments how to do the math.png [ 723.33 KiB | Viewed 882 times ]

Senior Manager  P
Joined: 29 Jun 2017
Posts: 417
GPA: 4
WE: Engineering (Transportation)
Re: In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X  [#permalink]

### Show Tags

solve the given x(1+x(1+x(1+x(1+x)))
count the min power of x , which will be x^1
now the An/ expression = x^5
means x^1 x x^ 5 = x ^ 6 is min power of x
now see nth term.. least power expression is x^(n-1)
n-1=6, n=7
Manager  B
Joined: 24 Jan 2017
Posts: 66
Location: Brazil
Concentration: Strategy, Entrepreneurship
GPA: 3.5
WE: Consulting (Consulting)
Re: In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X  [#permalink]

### Show Tags

KarishmaB wrote:
subhashghosh wrote:
Hi Karishma

What is the meaning of this ?

"it means the part: (1+x(1+x(1+x(1+x)))) will get canceled from the num and den."

Regards,
Subhash

$$A2 = x + x^2 + x^3 + x^4 + x^5$$

$$\frac{An}{{x(1+x(1+x(1+x(1+x))))}} = x^5$$
Since the right side of the equation is just x^5, it means the entire expression: (1+x(1+x(1+x(1+x)))) should get canceled out which means we will get the same expression in the numerator as well. You don't need to do it. It is logical since otherwise, you will not get the reduced expression x^5. Also, you can see that you will get something like this in the numerator since the powers are increasing.

If you want to see it:
$$A2= x( 1 + x + x^2 + x^3 + x^4) = x( 1 + x(1 + x + x^2 + x^3)) = x( 1 + x(1 + x( 1 + x + x^2))) = x( 1 + x(1 + x( 1 + x( 1 + x))))$$

Similarly A7 $$= x^6( 1 + x(1 + x( 1 + x( 1 + x))))$$

So $$\frac{A7}{{x(1+x(1+x(1+x(1+x))))}} = \frac{x^6( 1 + x(1 + x( 1 + x( 1 + x))))}{x( 1 + x(1 + x( 1 + x( 1 + x))))}= x^5$$

KarishmaB Can you explain how to do this step: A2= x( 1 + x + x^2 + x^3 + x^4) = x( 1 + x(1 + x + x^2 + x^3)) = x( 1 + x(1 + x( 1 + x + x^2))) = x( 1 + x(1 + x( 1 + x( 1 + x))))

I don't get it! (

Tks!!!
Intern  B
Joined: 07 Jun 2018
Posts: 20
Location: India
GPA: 3.9
WE: Marketing (Insurance)
Re: In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X  [#permalink]

### Show Tags

Loved the question. Solve it in under 1.5 min. Tricky. If one can understand the pattern, anything more than a minute is waste.
Veritas Prep GMAT Instructor V
Joined: 16 Oct 2010
Posts: 9850
Location: Pune, India
Re: In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X  [#permalink]

### Show Tags

subhashghosh wrote:
Hi Karishma

What is the meaning of this ?

"it means the part: (1+x(1+x(1+x(1+x)))) will get canceled from the num and den."

Regards,
Subhash

$$A2 = x + x^2 + x^3 + x^4 + x^5$$

$$\frac{An}{{x(1+x(1+x(1+x(1+x))))}} = x^5$$
Since the right side of the equation is just x^5, it means the entire expression: (1+x(1+x(1+x(1+x)))) should get canceled out which means we will get the same expression in the numerator as well. You don't need to do it. It is logical since otherwise, you will not get the reduced expression x^5. Also, you can see that you will get something like this in the numerator since the powers are increasing.

If you want to see it:
$$A2= x( 1 + x + x^2 + x^3 + x^4) = x( 1 + x(1 + x + x^2 + x^3)) = x( 1 + x(1 + x( 1 + x + x^2))) = x( 1 + x(1 + x( 1 + x( 1 + x))))$$

Similarly A7 $$= x^6( 1 + x(1 + x( 1 + x( 1 + x))))$$

So $$\frac{A7}{{x(1+x(1+x(1+x(1+x))))}} = \frac{x^6( 1 + x(1 + x( 1 + x( 1 + x))))}{x( 1 + x(1 + x( 1 + x( 1 + x))))}= x^5$$

Quote:
Hi! Can you please explain me how to do this step: A2= x( 1 + x + x^2 + x^3 + x^4) = x( 1 + x(1 + x + x^2 + x^3)) = x( 1 + x(1 + x( 1 + x + x^2))) = x( 1 + x(1 + x( 1 + x( 1 + x))))

You are just taking out x's common from the remaining terms one after the other.

A2= x( 1 + x + x^2 + x^3 + x^4)

= x( 1 + x(1 + x + x^2 + x^3))

= x( 1 + x(1 + x( 1 + x + x^2)))

= x( 1 + x(1 + x( 1 + x( 1 + x))))
_________________
Karishma
Veritas Prep GMAT Instructor

Non-Human User Joined: 09 Sep 2013
Posts: 13724
Re: In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X  [#permalink]

### Show Tags

Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________ Re: In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X   [#permalink] 21 Aug 2019, 08:35

Go to page   Previous    1   2   [ 30 posts ]

Display posts from previous: Sort by

# In the infinite sequence A, An = X^(n-1) + X^n + X^(n+1) + X^(n+2) + X  